Excluded. A Digital Ethnographic Investigation on the Femcel Community - Pizzimenti, Debora Maria; Penna , Assunta (Italian Sociological Review, 2024)
The paper purpose is to explore the feelings of exclusion and anger expressed on digital platforms by a community of women identifying within the Femcel subculture. The term “Femcel” is a portmanteau of “female” and “incel” (involuntary celibate), referred to women unable to obtain romantic or sexual relationships despite their desires and efforts. This sense of frustration, within the realm of digital communications, is heightened by the architecture of platforms, which reinforces and perpetuates existing power hierarchies, confining individuals within echo chambers. This paper analyses the most important online Femcel communities on Reddit, named “Vindicta”, through digital ethnography facilitated by the NVivo software. The body of academic literature addressing women’s distress to sexual inadequacy is insufficient; conversely, male Incels have garnered scholarly and journalistic attention for their lack of sexual capital. The study has underscored that despite Incel women being considered unattractive and “undesirable”, they lament the lack of authorization to lay claim to an identity based on this state of abjection. This is due to the presumption that any woman could seduce a man if she really wanted to, consequently disregarding the recognition of the Femcel figure as a legitimate identity, in contrast to the treatment of male Incels.